Appendiceal pseudomyxoma peritonei: predictors of recurrence and iterative surgery. (12th July 2021) - Kong, Joseph C.; Flood, Michael P.; Guerra, Glen R.; Liesegang, Amanda; Wong, Wen J.; Mitchell, Catherine; Warrier, Satish K.; Naidu, Sanjeev; Meade, Brian; Lutton, Nicholas; Heriot, Alexander G.
Abstract: Aim: Appendiceal pseudomyxoma peritonei (PMP) is a rare entity, with recurrence rates up to 26% despite optimal cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Evidence specific to PMP originating from non‐infiltrative appendiceal mucinous neoplasms (low grade ‐ LAMN and high grade ‐ HAMN) is lacking. The aim of this study was to identify patterns of recurrence and predictive factors for patients appropriate for iterative surgery. Method: A bi‐institutional retrospective analysis was performed on patients undergoing complete cytoreduction and HIPEC for PMP derived from perforated LAMN or HAMN. Multivariate logistic regression was performed to identify independent predictors for re‐do CRS. Five‐year overall survival (OS) was stratified according to surgical intervention, and 5‐year disease‐free survival (DFS) was stratified according to histological PMP grade. Cox regression analysis was performed to identify independent predictors for OS and DFS. Results: Sixty of 239 (25.1%) patients developed peritoneal recurrence between 2007 and 2020. The median time to recurrence was 20.7 months. The risk of disease recurrence was highest with high‐grade PMP ( P <0.001) and increasing PCI ( P <0.001). Patients with high‐grade histology from their index procedure and aged over 60 years were less likely to be offered iterative surgery on multivariate analysis. Patients who underwent iterative CRS and HIPEC had a 5‐year survival of 100%. Conclusion: Iterative CRS and HIPEC is feasible in selected patients with recurrent PMP, displaying good oncological outcomes. Age, index histology and level of abdominal quadrant involvement are predictive of proceeding to re‐do surgery.